The complete mitochondrial genome of Orthaga achatina (Lepidoptera: Pyralidae) - Liu, Bing (Mitochondrial DNA B Resour, 2021)
Orthaga achatina Butler is an important pest of camphor trees in Asia. The complete mitochondrial genome of O. achatina was sequenced in this study, which was 15,150 bp in size and comprised of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a control region. Besides, we used a phylogenomic approach to infer evolutionary relationships of O. achatina and 23 Lepidoptera species based on 13 conserved protein sequences of the mitochondrial genome. Our results underline the potential importance of mitochondrial genomes in comparative genomic analyses of Lepidoptera species and provide a robust evolutionary insight across the tree of Lepidoptera insects.